The Management of Complex Tasks in Organizations: Controlling the Systems Development Process - Kirsch, Laurie J. (Organization Science, 1996)
Control theory attempts to explain how one person or group in an organization can ensure that another person or group works toward and attains a set of organizational goals. Prior empirical work investigating control theory has shown that characteristics of the task and of the organizational environment predict the use of various types of control. However, this paper argues that when control theory is applied to a complex, nonroutine task such as the management of information systems development, the theory of control is incomplete. In particular, it proposes that knowledge of the task is a key determinant of type of control. Four modes of control (behavior, outcome, clan, and self) art identified from the organizational literature; each high-lights different aspects of control in organizations. Building on prior empirical work, this paper integrates the different theoretical perspectives and predicts the circumstances under which each type of control will be implemented. Survey responses from 96 participants of 32 systems development efforts suggest that the extent to which behaviors are monitored interacts with the project sponsor's level of systems development knowledge to determine the amount of behavior control; that outcome control is a function of the extent to which behaviors are monitored and outcomes are measurable; and that self-control is dependent on the extent to which outcomes are measurable and the level of the project sponsor's knowledge about systems development activities. No relationship between clan control and the independent variables was found.